2011
DOI: 10.3109/09638288.2010.508829
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stroke: are people with aphasia different to those without?

Abstract: Citation: Hilari, K. (2011). The impact of stroke: are people with aphasia different to those without?. Disability and Rehabilitation, 33(3), pp. 211-218. doi: 10.3109/09638288.2010.508829 This is the unspecified version of the paper.This version of the publication may differ from the final published version. 3 Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
1
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(166 citation statements)
references
References 27 publications
8
147
1
10
Order By: Relevance
“…Similar conclusions were drawn by Gialanella [24]. Hilari in the study published in 2011, which compared patients with and without aphasia, found that patients with aphasia are less active, and their quality of life is worse than patients without aphasia, even if their functional state, welfare and social support are comparable [25]. The severity of aphasia is a strong predictor of long-term mortality and observed during a period of 12 months dependency of patients with aphasia compared with those without aphasia [26].…”
Section: Discussionsupporting
confidence: 73%
“…Similar conclusions were drawn by Gialanella [24]. Hilari in the study published in 2011, which compared patients with and without aphasia, found that patients with aphasia are less active, and their quality of life is worse than patients without aphasia, even if their functional state, welfare and social support are comparable [25]. The severity of aphasia is a strong predictor of long-term mortality and observed during a period of 12 months dependency of patients with aphasia compared with those without aphasia [26].…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, internal validity, interrater reliability, and the time required for scale completion were determined in "acute" patients. Finally, LAST was primarily designed to evaluate language impairment, but it is now well recognized that the impact on daily life activities of such impairments extends beyond these actual impairment, 36 and tools have recently been developed to specifically address this issue. 37,38 It would be interesting to test LAST against such quality-oflife scales.…”
Section: Discussionmentioning
confidence: 99%
“…It is also clear in the studies that the aphasic has a higher number of depression symptoms, difficulties in performing daily activities, and higher level of dependence (15,20,27,29,30) . Moreover, the aphasic's condition limits social relations (7,27) , which explains the findings.…”
Section: Discussionmentioning
confidence: 99%